DOMESTIC COMPONENT LEVEL ASSESSMENT FOR A SALT FACTORY AND A SALT PRODUCTION - Febijanto, Irhan; Adiarso; Ati Widiati; Dharmawan; Dadang Rosadi; Ermawan Darma; Gatyo Angkoso; Karnadi; Kusrestuwardhani; Mohamad Soleh Iskandar; Nurus Sahari Laili; Priyambodo Darmoyuwono; M.Rosjidi; Sunengsih (Majalah Ilmiah Pengkajian Industri, 2021)
The TKDN (Domestic Component Level) assessment of goods and services is a method to determine local manufacturers/industrie’s capability to create quality products internationally standardized. This study assessed the salt factory's TKDN to increase the NaCl content, based on cost-based analysis stipulated at the Minister Industry Regulation No.16/M-IND/PER/2/2011. Meanwhile, the TKDN of salt production was assessed based on process-based analysis stipulated in Minister Industry Regulation No.16/2020. According to the cost-based analysis results, the goods and services at the pilot project stage had the TKDN value of 27.4%. However, due to an increase in the number of main domestic components at the commercial stage, this value increased to 70.9%. Meanwhile, according to the processed-based analysis results, the salt production had the same processes at the pilot project stage and commercial stages. The TKDN value of 85.5% was obtained for the two stages. The value is relatively high because the raw material is produced locally with the local labor and used work tools owned by the local industry. The cost-based analysis was found to be highly dependent on the equipment component’s origin, while the process-based analysis depends on the origin of labor, works tool, and material owner. Keywords: domestic component level; process-based analysis; cost-based analysis; salt factory; salt product.